Social wellbeing: a positive energy for wellness in medical students - Rehman, Rehana; Hussain, Mehwish; Syed, Fatima; Khan, Rakhshaan (Journal of Postgraduate Medical Institute, 2014)
Objective: The objective of the study was to compare the level of socialawareness amongst medical students of public and private medical universitiesof Karachi - Pakistan.Methodology: It was a cross sectional, questionnaire based study which randomlyrecruited 800 medical students from three government and five privatemedical colleges. Their responses on various aspects of social wellnesswere graded from 0-4 (never, sometimes, mostly and always). Non-parametricmethods were employed for the comparison of social wellness between thestudents of two types of institutes. Factor analysis was run to extract commonfactors in our setup.Results: Students from public and private medical universities (public MU/private MU) acquired significantly similar scores on communication wellness.Both group of students reported that they had network of close acquaintances.Students from public institutes not only showed a significant problemssolving attitude to help their fellows but also exhibited significant franknessand fairness while dealing with their social bounds. On the other hand theprivate MU students contributed more social time and money to communityprojects.Conclusion: Strategies should be made to involve public MU students in communityprojects. Private MU students need to be taught to care for their socialbounds and enhance activities to share their beings with friends and family.